Ground reaction force and valgus knee loading during landing after a block in female volleyball players - Zahradnik, D.; Uchytil, J.; Farana, R.; Jandacka, D. (Journal of Human Kinetics, 2014)
A non-contact anterior cruciate ligament (ACL) injury is both a serious and very common problem in volleyball. The aim of the study was to determine the association between stick, step-back, and run-back landings after a block and select risk factors of ACL injuries for female professional volleyball players. The research sample involved fourteen female professional volleyball players. Two force plates were used to determine ground reaction forces. Eight infrared cameras were employed to collect the kinematic data. The one-factor repeated-measures analysis of variance, where the landing type was the factor, was used for comparing the valgus moment and ground reaction force on the right lower limb. ANOVA showed that the type of landing has a main effect on the valgus moment on the right lower limb (F) = 5.96, p = 0.019df = 1.18, partial ?2 = 0.239 and SP = 0.693). Furthermore, it did not show a main effect on the vertical reaction force on the right lower limb ((F)=2.77, p=0.090, df=1.55, partial ?2= 0.128 and SP=0.448). The highest valgus moment occurred during the run-back landing. This moment, however, did not have any effect within the first 100 ms after initial contact with the ground, but rather upon the subsequent motion carried out when stepping back off the net. A comparison between a run-back landing and a step-back landing showed relevant higher values of vertical ground reaction forces during the run-back landing